Keywords the new language of capitalism - Leary, John. (Chicago Haymarket Books, 2018)
Keywords: The New Language of Capitalism chronicles the rise of a new vocabulary in the twenty-first century. From Silicon Valley to the White House, from kindergarten to college, and from the factory floor to the church pulpit, we are all called to be innovators and entrepreneurs, to be curators of an ever-expanding roster of competencies, and to become resilient and flexible in the face of the insults and injuries we confront at work. In the midst of increasing inequality, these keywords teach us to thrive by applying the lessons of a competitive marketplace to every sphere of life. What?s more, by celebrating the values of grit, creativity, and passion at school and at work, they assure us that economic success is nothing less than a moral virtue.
Keywords: Capitalism